2015
DOI: 10.1371/journal.pone.0119579
|View full text |Cite
|
Sign up to set email alerts
|

Gulf War Agent Exposure Causes Impairment of Long-Term Memory Formation and Neuropathological Changes in a Mouse Model of Gulf War Illness

Abstract: Gulf War Illness (GWI) is a chronic multisymptom illness with a central nervous system component such as memory deficits, neurological, and musculoskeletal problems. There are ample data that demonstrate that exposure to Gulf War (GW) agents, such as pyridostigmine bromide (PB) and pesticides such as permethrin (PER), were key contributors to the etiology of GWI post deployment to the Persian GW. In the current study, we examined the consequences of acute (10 days) exposure to PB and PER in C57BL6 mice. Learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
77
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 72 publications
9
77
1
Order By: Relevance
“…Histopathological analyses of this PB+PER mouse model revealed an increase in astroglia activation in exposed mice (Abdullah et al, 2011;Zakirova et al, 2015), which is also observed in several other rodent models of GWI (Abdullah et al, 2012;Abdullah et al, 2011;Zakirova et al, 2015;Parihar et al, 2013;Ojo et al, 2014). In the brain, astroglia play a fundamental role in providing support to neurons by maintaining the extracellular environment and delivering nutrients to neurons that are acquired from the peripheral circulation.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…Histopathological analyses of this PB+PER mouse model revealed an increase in astroglia activation in exposed mice (Abdullah et al, 2011;Zakirova et al, 2015), which is also observed in several other rodent models of GWI (Abdullah et al, 2012;Abdullah et al, 2011;Zakirova et al, 2015;Parihar et al, 2013;Ojo et al, 2014). In the brain, astroglia play a fundamental role in providing support to neurons by maintaining the extracellular environment and delivering nutrients to neurons that are acquired from the peripheral circulation.…”
supporting
confidence: 62%
“…GWI, identifying molecular changes in the brain necessitates the use of well-established animal models of GWI. We developed a GWI mouse model using combined exposure to PB and PER that exhibits anxiety and cognitive problems that are similar to the symptoms reported by veterans with GWI (White et al, 2016;Abdullah et al, 2011;Zakirova et al, 2015;Sullivan et al, 2003). Hence, this mouse model captures one of the key clinical features of GWI and is suitable for examining long-term changes that are relevant to the current clinical condition of veterans with GWI.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…As reported above, the PB+PER mouse model and the PB+PER+DEET and stress rat model utilized in this study have been well characterized with respect to neurobehavioral features that are similar to chronic symptoms reported by GWI patients [9,10,41,44,47]. Samples from both rodent models were collected at 6 months post exposure.…”
Section: Discussionmentioning
confidence: 97%